Penerapan Kompres Kompres Es untuk Mengurangi Nyeri pada Ibu Pascapersalinan dengan Luka Episiotomi: Studi Kasus - Jannah, Fitriani Yusayyirotul; Oktafia, Riski (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Problems that often occur in postpartum women cause pain and discomfort, one of which is perineal episiotomy during labor to facilitate delivery of the baby. Injury to the perineum can affect the mother's discomfort after giving birth, interfere with activities and be at risk for infection. One of the interventions carried out is non-pharmacological pain management which can reduce pain in the perineum by using ice packs. The purpose of this study was to see the effectiveness of using ice packs in reducing pain in episiotomy wounds in postpartum women. This research is a case study on postnatal patients with episiotomy wounds. Prior to compressing the ice pack, pain levels were measured using a numerical rating scale (NRS). After the compress intervention was carried out using an ice pack with a duration of 24 hours with a span of 2 days. The results of the intervention, namely at the time of the initial measurement before the intervention, the patient's pain scale 7 was included in the severe pain category. After intervention was found using ice packs, pain in the perineal area was reduced to a scale of 3, included in the mild pain category. The use of ice packs is effective in reducing postpartum episiotomy wound pain and can be applied by health workers in the delivery room and postpartum ward. After intervention was found using ice packs, pain in the perineal area was reduced to a scale of 3, included in the mild pain category. The use of ice packs is effective in reducing postpartum episiotomy wound pain and can be applied by health workers in the delivery room and postpartum ward. After the intervention of compresses using ice packs was found, pain in the perineal area was reduced to a scale of 3 which was included in the mild pain category. The use of ice packs is effective in reducing postpartum episiotomy wound pain and can be applied by health workers in the delivery room and postpartum ward.